The Lexicon Associated with the Description of Slaves in Notarial Records of Central Cuba (1860) - Peña Olmo, Roxana; Martínez Cruz, Karen María (Espergesia, 2025)
The following paper presents partial results of a study on the lexical associated with the description of slaves in a corpus of notarial protocols belonging to Sagua la Grande (1860), present-day municipality of Villa Clara, Cuba. For this case, a corpus of documents related to matters of freedom and buying and selling will be treated. In the analysis it has been taken into account the use of the methods of the theoretical level: the historical-logical, the analytical-synthetic, the inductive-deductive; of the empirical level: the bibliographical review; and as a technique: document analysis. These are used for the selection and interpretation of data, both in the theoretical materials consulted for reference and in the corpus. The perspective presented contributes to the rescue and interpretation of the Cuban historical and linguistic memory in the second half of the 19th century from the study of foreign and own elements of the lexical repertoire of Cuban Spanish and its analysis in the central zone. In addition, it serves to understand how power relations, property and hierarchy are articulated in this period according to ethnic origin through the language documented in the selected texts. The lexical repertoire analyzed refers to elements such as: physical features, ethnic origin with a predominance of Creole lineage, and conditions under which the link with landowners and lucrative exchange takes place. Its composition, schematic in form and repetitive in discourse, allows to obtain a limited but significant corpus for analysis.